2022
DOI: 10.53894/ijirss.v5i1.334
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Computer-Aided Diagnosis of Neonatal Hyperbilirubinemia using Digital Image Processing and Machine Learning Techniques

Abstract: Neonatal Hyperbilirubinemia, or jaundice, is a harmful disease found in newborns, a symptom of which is the yellowish discoloration of the skin. Visual examination is most frequently used for screening of Hyperbilirubinemia in neonates, however, blood specimen collection is the gold standard to identify the disease and its severity. We propose a Mobile Computer-Aided Diagnosis (mCADx) tool to identify the Neonatal Hyperbilirubinemia symptom using advanced digital image processing and data mining techniques. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Different machine learning methods, such as an www.aetic.theiaer.org ensemble of different classifiers, checking KNN, LARS-Lasso elastic net, LARS, SVR, and RF, have been employed to ensure jaundice. Using methods for sophisticated digital image processing and data mining, Dissaneevate et al [47] suggested a Mobile Computer-Aided Diagnosis (mCADx) tool to diagnose the Neonatal Hyperbilirubinemia symptom. They explored data mining approaches using the dataset, including Decision Trees, k Nearest Neighbors, and the Conventional Neural Network, on picture data of 178 infant participants with varying degrees of jaundice severity.…”
Section: Methodologies Of Neonatal Jaundice Detectionmentioning
confidence: 99%
“…Different machine learning methods, such as an www.aetic.theiaer.org ensemble of different classifiers, checking KNN, LARS-Lasso elastic net, LARS, SVR, and RF, have been employed to ensure jaundice. Using methods for sophisticated digital image processing and data mining, Dissaneevate et al [47] suggested a Mobile Computer-Aided Diagnosis (mCADx) tool to diagnose the Neonatal Hyperbilirubinemia symptom. They explored data mining approaches using the dataset, including Decision Trees, k Nearest Neighbors, and the Conventional Neural Network, on picture data of 178 infant participants with varying degrees of jaundice severity.…”
Section: Methodologies Of Neonatal Jaundice Detectionmentioning
confidence: 99%
“…Almost 60% of term neonates and 80% of preterm neonates develop symptoms of jaundice [ 1 ]. It is observed that when the bilirubin level exceeds 5 mg/dL, it leads to yellow discoloration of the sclera and skin, and an increase in the level may lead to Kernicterus or cause death [ 2 ]. The most common treatment for this increased bilirubin, or hyperbilirubinemia, is either phototherapy or exchange transfusion [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dissaneevate et al introduced a Mobile Computer-Aided Diagnosis (mCADx) platform, employing decision trees, k-nearest neighbor, and convolutional neural networks (CNNs), with the CNN achieving the highest accuracy [ 2 ]. Sammir et al created a portable monitoring system capturing sclera images with a custom goggle, achieving a 90% accuracy rate [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their results include changes in diameter and thickness with stress distribution for both monolayer and bilayer mod-els, indicating a major di erence between monolayer and bilayer models in stress distribution. In [23], the stress distribution in the abdominal aortic aneurismal wall was investigated using nite element modeling. The results of this study indicate that in addition to the size of the aneurysm, mechanical properties and blood ow may also signi cantly a ect the stress distribution in the aneurismal wall.…”
Section: Introductionmentioning
confidence: 99%